Intracranial arterial abnormalities in patients with late onset Pompe disease (LOPD). Issue 3 (1st February 2016) - Montagnese, Federica; Granata, Francesca; Musumeci, Olimpia; Rodolico, Carmelo; Mondello, Stefania; Barca, Emanuele; Cucinotta, Maria; Ciranni, Anna; Longo, Marcello; Toscano, Antonio
Abstract: Background and objectives: Pompe disease is a rare metabolic disorder due to lysosomal alpha‐glucosidase (GAA) deficiency. It is considered as a multi‐systemic disease since, although glycogen accumulation is largely prominent in heart, skeletal and respiratory muscles, other organs can also be affected. As regards the vascular system, few reports have documented cerebrovascular malformations in Pompe patients. The aim of this study was to define the presence and type of intracranial arterial abnormalities in a cohort of late onset Pompe disease (LOPD) patients. Methods: We have studied 21 LOPD patients with cerebral CT angiography (CTA), using maximum intensity projection and volume rendering technique for 3D‐image reconstruction. Results: We found intracranial arterial abnormalities in 13/21 patients (62 %), of whom: 2/21 patients (9.5 %) showed an unruptured intracranial aneurysm (respectively 2 and 4 mm), 10/21 (47 %) had a vertebrobasilar dolichoectasia (VBD) and 1/21 a basilar artery fenestration. Signs of lacunar encephalopathy (insular, capsular and frontal subcortical lesions) were detected in 13/21 patients (62 %) and this correlated with the presence of respiratory impairment ( p  = 0.017). Conclusions: These findings differ from what has been previously observed in healthy, aged‐matched populations and confirm that cerebral arteries abnormalities, mainly involving the posterior circle, are not so rare in LOPD patients and are often accompanied by a lacunar encephalopathy that might represent a hypoxic‐ischemic origin. A CTA or an MRA is recommended, in LOPD patients, for early detection of cerebrovascular malformations as they could lead to life‐threatening events such as sub‐arachnoid haemorrhage or brainstem compression.